ORGANIZATION AND PLANNING IN CHILDREN WITH ADHD: EVALUATION AND PROPOSAL OF A STIMULATION PROGRAM - Josefina Rubiales; Liliana Bakker; Iván Darío Delgado Mejía (CAEN, 2011)
The Attention Deficit Hyperactivity Disorder (ADHD) is a neurobiological disorder of a complex and heterogeneous origin characterized by a persistent pattern of inattention, hyperactivity and / or impulsivity. Is one of the most common neurobehavioral disorders in childhood and adolescence, and one of the main reasons for consultation because of difficulties in school performance, behavior problems, difficulties of living at home and with peers, involvement in self-esteem and aggressiveness. The primary deficit is associated with executive dysfunction, among which is the organization and planning. The aim of this study was to compare the performance in organization and planning of children with and without a diagnosis of ADHD and submit a stimulation proposal according to their needs. MATERIALS AND METHODS: The clinical sample comprised 16 children diagnosed with ADHD and the control sample of 32 children without a diagnosis, in both cases 8 to 14 years old and from the city of Mar del Plata (Argentina). The instruments used to evaluate the organization and planning has been the subtest Torres of Mexico Child Neuropsychological Battery (ENI), and cubes subtests Construction, Completion and Management Object Test Story Weschler Intelligence for children and adolescents. The proposed treatment includes 8 sessions of stimulation. RESULTS AND CONCLUSIONS: Children with ADHD have greater difficulty in planning and organizational skills than the children of the control sample, from which it establishes a estimulation proposal, whose originality and advantage is accentuated in the ecological validity the process.